Influence of the charge of 1,3,5-triaza-7-phosphaadamantane-based ligands on the anticancer activity of organopalladium complexes - Lorenzon, Tommaso; Vescovo, Maria; Maiullari, Michele; Tonon, Giovanni; Conceição, Nuno Reis; Carabineiro, Sónia A.C.; Mahmoud, Abdallah G.; Dietl, Martin C.; Demitri, Nicola; Orian, Laura; Nogara, Pablo A.; Caligiuri, Isabella; et al. (RSC Advances, 2025)
In this study, we report the synthesis and characterization of novel organopalladium complexes featuring 1,3,5-triaza-7-phosphaadamantane (PTA)-based ligands, including several cationic derivatives prepared as hexafluorophosphate salts to prevent halide exchange reactions. The complexes incorporate diverse organopalladium fragments—Pd(II)-vinyl, Pd(II)-butadienyl, Pd(II)-allyl, Pd(II)-imidoyl, Pd(II)-aryl, and Pd(0)-alkene—many of which have recently shown promising antitumor activity. Most reactions proceeded rapidly at room temperature under aerobic conditions using non-anhydrous solvents. Biological evaluation against ovarian cancer (A2780), cisplatin-resistant ovarian cancer (A2780cis), triple-negative breast cancer (MDA-MB-231), glioblastoma (U87), and non-cancerous fibroblasts (MRC-5) revealed the remarkable cytotoxicity of the complexes, particularly those with Pd(II)-butadienyl, Pd(II)-aryl, and Pd(0)-alkene fragments. These compounds demonstrated activity comparable to or exceeding cisplatin, with some showing up to two orders of magnitude greater efficacy. Importantly, the complexes were highly selective for cancer cells, exhibiting minimal toxicity toward MRC-5 fibroblasts, unlike cisplatin. Complex 14b, that contains a Pd(0)-alkene fragment and two MePTA+ ligands, was the only one that exhibited excellent cytotoxicity across all cancer cell lines, including glioblastoma. These findings underscore the potential of PTA-based organopalladium complexes as selective anticancer agents, warranting further in vitro and in vivo studies, as well as mechanistic investigations.
Gesehen am 04.11.2025